2010
DOI: 10.1088/0004-637x/725/2/1955
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Peak-Flux Distribution of the Third Class of Gamma-Ray Bursts: A Possible Signature of X-Ray Flashes?

Abstract: Gamma-ray bursts are the most luminous events in the Universe. Going beyond the short-long classification scheme we work in the context of three burst populations with the third group of intermediate duration and softest spectrum. We are looking for physical properties which discriminate the intermediate duration bursts from the other two classes. We use maximum likelihood fits to establish group memberships in the duration-hardness plane. To confirm these results we also use k-means and hierarchical clusterin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 39 publications
5
75
0
Order By: Relevance
“…This was confirmed from further analysis of the complete BATSE dataset (Horváth 2002;Chattopadhyay et al 2007;Zitouni et al 2015). Evidence for a third lognormal component was also found in Swift/BAT data (Horváth et al 2008;Huja et al 2009;Horváth et al 2010) using duration and also from two-dimensional clustering using both duration and hardness (Veres et al 2010 Horváth & Tóth (2016), who pointed that three lognormal distributions provide a better fit to the data than two with 99.9999% confidence level. Tarnopolski (2016a) finds that for the similar Swift GRB dataset consisting of 947 GRBs, three groups are favored in the observer frame, whereas two in the rest frame.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…This was confirmed from further analysis of the complete BATSE dataset (Horváth 2002;Chattopadhyay et al 2007;Zitouni et al 2015). Evidence for a third lognormal component was also found in Swift/BAT data (Horváth et al 2008;Huja et al 2009;Horváth et al 2010) using duration and also from two-dimensional clustering using both duration and hardness (Veres et al 2010 Horváth & Tóth (2016), who pointed that three lognormal distributions provide a better fit to the data than two with 99.9999% confidence level. Tarnopolski (2016a) finds that for the similar Swift GRB dataset consisting of 947 GRBs, three groups are favored in the observer frame, whereas two in the rest frame.…”
Section: Introductionsupporting
confidence: 63%
“…Tarnopolski (2016a) finds that for the similar Swift GRB dataset consisting of 947 GRBs, three groups are favored in the observer frame, whereas two in the rest frame. The possible physical origin of the third intermediate class of Swift GRBs is attributed to X-ray flashes (Veres et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A solution, proposed to deal with the classification ambiguity problem, was proposed and examined in a number of papers (Hakkila et al 2003;Horváth et al 2004Horváth et al , 2006Horváth et al , 2010Chattopadhyay et al 2007;Veres et al 2010). The idea is to examine a multi-dimensional space of various parameters; particularly, a two-dimensional space of the hardness ratio vs. duration T 90 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Mészáros et al (2000a,b); Litvin et al (2001); Bernui et al (2008); Veres et al (2010a); Ukwatta & Woźniak (2016) claimed different results. The pertinent intermediateduration GRBs (2 s T 90 10 s) (Mukherjee et al 1998;Horváth 1998;Balastegui et al 2001;Horváth 2002;Horváth et al 2008;Horváth 2009;Huja et al 2009;Řípa et al 2009;Horváth et al 2010;Veres et al 2010b;de Ugarte Postigo et al 2011;Řípa et al 2012;Zitouni et al 2015;Horváth & Tóth 2016;Řípa & Mészáros 2016;Yang et al 2016;Kulkarni & Desai 2017) were found to be distributed anisotropically on the sky (Mészáros et al 2000a,b;Litvin et al 2001;Vavrek et al 2008;Veres et al 2010a). However, Mészáros &Štoček (2003); Ukwatta & Woźniak (2016) claimed different results.…”
mentioning
confidence: 99%